Washington View: Big change on both sides of the pond. (March 2017) - Ferguson, Maria
Seismic shifts in both the United States and the United Kingdom during the 2016 elections have introduced changes in the education space as well. Worries about jobs, immigration, and shifting demographics underlie policy proposals in both countries. Where the U.S. is trying to drive change to the state and local level, however, Britain is moving toward centralization .